Never Getting Off the Ground or Heading Home Early : Student Perceptions and Experiences of Study Abroad Disruption During COVID-19 (Comparative & International Education Series, 2021)
Study abroad has long been shown to be a formative and meaningful student experience. In an increasingly globalized world, many universities have not only taken steps to expand study abroad opportunities, but also to formally integrate these experiences into the broader university curriculum and mission. However, the realities of the COVID-19 pandemic mean many students have had to cancel or prematurely return home from their planned study abroad. This chapter uses original survey and focus group data to examine how students make sense of these canceled and abbreviated cross-cultural experiences in the context of COVID-19. Written from the unique perspective of one of the only colleges with an undergraduate study abroad requirement, this chapter asks: What lessons do students take from canceled/abbreviated international experiences? How do they evaluate their interactions with their home institution during this process? Finally, how does this experience impact students’ views of study abroad requirements?